Analysis of the volatile compounds associated with pickling of ginger using headspace gas chromatography ‐ ion mobility spectrometry. (29th August 2019) - Li, Xiao; Cui, Wenjia; Wang, Wenliang; Wang, Yueming; Gong, Zhiqing; Xu, Zhixiang
Abstract: Pickled ginger is a popular traditional Chinese pickled food. Analysis of the volatile compounds in pickled ginger is critical for guiding production, achieving a high level of sensory quality, and maintaining a healthy diet. Ion mobility spectrometry (IMS) with gas chromatography (GC) offers a fast, sensitive, and efficient tool for detecting volatile compounds. Herein, the headspace GC‐IMS method was used to detect the volatile flavour compounds produced during the pickling of ginger. The ion mobility data were continuously processed using the principal component analysis (PCA) and fingerprint chart methods. Based on the analysis of fresh ginger, pickled ginger, and soy sauce, two main components accounted for 58% and 27% of the total variance. During pickling, the heptanal and heptanone contents decreased, while the contents of butanal, butanone, and methional increased, as determined from the GC‐IMS fingerprint, resulting in changes in the flavour of the pickled ginger. The GC‐IMS method was efficient, convenient, and useful for the detection of volatile flavour compounds produced during the ginger pickling process. Abstract : The GC‐IMS method was efficient, convenient, and useful for the detection of volatile flavour compounds produced during the ginger pickling process.